DEVELOPING MOTIVATION FOR LEARNING FOREIGN LANGUAGES (Web of Teachers: Inderscience Research, 2024)
This in-depth article addresses the difficulties teachers encounter while encouraging their students to learn a foreign language and offers practical strategies to raise motivation and engagement levels. It highlights how crucial it is to provide an engaging and customized learning environment by utilizing games, real-world resources, and communication exercises. It also covers how technology and cutting-edge techniques, like gamification, virtual reality, and online learning platforms, might promote motivation. The significance of using research and data analysis to evaluate the efficacy of motivational strategies is also covered in the text. All things considered; it is a useful tool for educators who aim to improve language acquisition results by using powerful motivational techniques.